PROSES PEMBUATAN PRESS HIDROLIK KAPASITAS MAKSIMAL 15 TON - Iik Hikmatul Akbar; Yudi Samantha; Engkos Koswara (PROCEEDING STIMA)
Hydraulic press tool is an apparatus used to suppress or install components with size specific pressure , so getting the expected results based on the specifications. Hydraulic press tool works by Pascal 's Law , how it works using a hydraulic system . A hydraulic press equipment consists of the basic components used in the hydraulic system that includes cylinders , pistons , hydraulic pipe , and others - others . The working principle of this press tool is very simple . The system consists of two cylinders , liquid ( usually oil ) is poured into the cylinder has a small diameter . Hydraulic Press Tool uses Hydraulic working system , the process works Hydraulic is very important in the Press and on the process of work is limited to 15 Tonnes corresponding hydraulic capacity is used.Keyword :Press tool, Hydraulic, Bearing